One- dimensional consolidation of modified peat soil - Arasavindiran, A/L Mariappan. (Universiti Malaysia Sarawak, UNIMAS, 2004)
Peat soil has been known to be the major group of problem soil in Malaysia. In Sarawak alone, peat covers 13% of the total land area. The main problem in peat is the excessive and differential settlement which results difficult design and construction condition. Furthermore, peat is difficult to sample and test using conventional method. One important characteristic that is important for analysis is the consolidation characteristic. This is because the consolidation behavior is related to the org anic content of the soil. Therefore, the aim of this study is to investigate the consolidation behaviors of peat, in particular the consolidation parameters with respect to the organic content and relationships. The Oedometer consolidation test equipment will be used to obtain the results and effects of organic content on the coefficient of consolidation (Cv), coefficient of compression index (Cc) and coefficient of volume compressibility (mv). From the experiments conducted, the value of Cv was found to be in the range of 0.094 to 0.848 cm 2 /min. Where as the value of mv was found to be decreasing as the organic content decreased. The value of Cc was also found to be decreasing as organic content decreased.